2008
DOI: 10.1097/pas.0b013e31816a3b42
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Stromal Sarcomas and Related High-grade Sarcomas: Immunohistochemical and Molecular Genetic Study of 31 Cases

Abstract: Classification and terminology of non-low-grade endometrial sarcomas, which show significant nuclear atypia, have been controversial. Currently, these tumors seem to be classified all together into "undifferentiated endometrial sarcoma (UES)." However, it remains unclear whether these non-low-grade sarcomas are universally "undifferentiated." We divided these sarcomas morphologically into undifferentiated endometrial sarcoma with nuclear uniformity (UES-U) and undifferentiated endometrial sarcoma with nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
188
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 177 publications
(206 citation statements)
references
References 22 publications
8
188
9
1
Order By: Relevance
“…1 These cases, other than the eight cases of endometrial stromal nodule, had been previously investigated in our study of immunohistochemical and molecular genetic analyses. 2 As we reported previously, 16 low-grade endometrial stromal sarcomas were mainly composed of uniform tumor cells resembling normal endometrial stromal cells with uniform nuclei showing minimal cytological atypia (Figure 1b). Of the 13 undifferentiated endometrial sarcoma, 7 featured rather monotonous cytological uniformity reminiscent of low-grade endometrial stromal sarcoma, but they were separated from lowgrade endometrial stromal sarcoma because they showed significant nuclear atypia (Figure 1c).…”
Section: Patients and Tissue Specimenssupporting
confidence: 71%
See 4 more Smart Citations
“…1 These cases, other than the eight cases of endometrial stromal nodule, had been previously investigated in our study of immunohistochemical and molecular genetic analyses. 2 As we reported previously, 16 low-grade endometrial stromal sarcomas were mainly composed of uniform tumor cells resembling normal endometrial stromal cells with uniform nuclei showing minimal cytological atypia (Figure 1b). Of the 13 undifferentiated endometrial sarcoma, 7 featured rather monotonous cytological uniformity reminiscent of low-grade endometrial stromal sarcoma, but they were separated from lowgrade endometrial stromal sarcoma because they showed significant nuclear atypia (Figure 1c).…”
Section: Patients and Tissue Specimenssupporting
confidence: 71%
“…As in our previous study, we call the former undifferentiated endometrial sarcoma group 'undifferentiated endometrial sarcoma with nuclear uniformity' and the latter group 'undifferentiated endometrial sarcoma with nuclear pleomorphism'. 2 …”
Section: Patients and Tissue Specimensmentioning
confidence: 99%
See 3 more Smart Citations